2019
DOI: 10.1128/aac.00755-19
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Clinical and Environmental Mycobacterium chimaera Isolates

Abstract: Mycobacterium chimaera is a slow-growing nontuberculous Mycobacterium species belonging to the Mycobacterium avium complex (MAC). It has been identified globally as the cause of a large outbreak of cardiovascular infections following open heart surgery, but it can also cause respiratory infections in individuals with underlying structural pulmonary disease. Invasive M. chimaera infections are associated with poor clinical responses, and the optimal antibiotic treatment regimen for these infections is not known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…In the current study, the susceptibility rates of all MAC species to clarithromycin and inhaled amikacin were 98.6% for both; however, the drug resistance rates were 32.6%, 85.5% and 91.5% for intravenous amikacin, moxifloxacin and linezolid, respectively. Consistent with the current findings, previous studies have indicated that clarithromycin demonstrates the best antimicrobial activity against common MAC species (Cho et al, 2018;Mok et al, 2019;Wei et al, 2015;Zhao et al, 2014). Reportedly, some studies have indicated low moxifloxacin and linezolid resistance rates in M. avium (Wei et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the current study, the susceptibility rates of all MAC species to clarithromycin and inhaled amikacin were 98.6% for both; however, the drug resistance rates were 32.6%, 85.5% and 91.5% for intravenous amikacin, moxifloxacin and linezolid, respectively. Consistent with the current findings, previous studies have indicated that clarithromycin demonstrates the best antimicrobial activity against common MAC species (Cho et al, 2018;Mok et al, 2019;Wei et al, 2015;Zhao et al, 2014). Reportedly, some studies have indicated low moxifloxacin and linezolid resistance rates in M. avium (Wei et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Reportedly, some studies have indicated low moxifloxacin and linezolid resistance rates in M. avium (Wei et al, 2015). However, most studies have reported higher moxifloxacin and linezolid resistance rates, which are similar to the current findings among the MAC isolates (Mok et al, 2019;Zhao et al, 2014). Compared with other species, it was observed that MAsH isolates demonstrated the lowest rate of resistance to moxifloxacin and, although 26.2% of MAC isolates were resistant to intravenous amikacin, most MAC isolates (98.6%) were still susceptible to inhaled amikacin.…”
Section: Discussionsupporting
confidence: 85%
“…It remains unclear whether the fact that post-CPB surgery infections have a common source of infection contributes to the particular AST pattern. Wild-type M. chimaera strains are susceptible to macrolides [7,15,95] and, to date, no isolate with clarithromycin resistance has been recovered [7,15,82]. One patient who received prolonged macrolide treatment and suffered infection relapse had an isolate that demonstrated intermediate resistance to clarithromycin (MIC of 16 to 32 mg/mL depending on pH) [52].…”
Section: Susceptibility To Antimicrobial Agentsmentioning
confidence: 99%
“…Because of the MIC distribution, doses up to 1800 mg/day were required to optimize the bactericidal effect, resulting in a high adverse event rate [95]. A recent publication testing antimicrobial susceptibilities of the newly recognized pathogen M. chimaera [96] [69], 15% and 18%, respectively, were resistant to linezolid.…”
Section: Oxazolidinonesmentioning
confidence: 99%
“…Because of the MIC distribution, doses up to 1800 mg/day were required to optimize the bactericidal effect, resulting in a high adverse event rate [ 95 ]. A recent publication testing antimicrobial susceptibilities of the newly recognized pathogen M. chimaera [ 96 ] demonstrated 39% of isolates (34/87 isolates) had intermediate susceptibility and 39% (34/87 isolates) were resistant to linezolid. Of 37 M. abscessus and M. fortuitum isolates tested by Zhang et al [ 69 ], 15% and 18%, respectively, were resistant to linezolid.…”
Section: Drugsmentioning
confidence: 99%